2016
DOI: 10.1016/j.cell.2016.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Host-Protozoan Interactions Protect from Mucosal Infections through Activation of the Inflammasome

Abstract: While conventional pathogenic protists have been extensively studied, there is an underappreciated constitutive protist microbiota that is an integral part of the vertebrate microbiome. The impact of these species on the host and their potential contributions to mucosal immune homeostasis remain poorly studied. Here, we show that the protozoan Tritrichomonas musculis activates the host epithelial inflammasome to induce IL-18 release. Epithelial-derived IL-18 promotes dendritic cell-driven Th1 and Th17 immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
320
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(335 citation statements)
references
References 52 publications
13
320
1
1
Order By: Relevance
“…These results together with the high expression of the IL-18 receptor IL-18Rα on colonic-infiltrating effector T cells suggested that T. musculis-specific T cell immunity is likely initiated in the draining lymph nodes by migratory colonic DCs and is likely propagated at the tissue site by epithelial IL-18 (91). Interestingly, T.…”
Section: Role Of the Protozoan Microbiota In Infection And Inflammationmentioning
confidence: 98%
“…These results together with the high expression of the IL-18 receptor IL-18Rα on colonic-infiltrating effector T cells suggested that T. musculis-specific T cell immunity is likely initiated in the draining lymph nodes by migratory colonic DCs and is likely propagated at the tissue site by epithelial IL-18 (91). Interestingly, T.…”
Section: Role Of the Protozoan Microbiota In Infection And Inflammationmentioning
confidence: 98%
“…These now include protozoans such as Tritrichomonas spp 67, 68 . and a human isolate of Bifidobacterium adolescentis 69 .…”
Section: Segmented Filamentous Bacteria (Sfb) and Reproducibilitymentioning
confidence: 99%
“…Animals from different sources are now well known to have very different commensal composition [11, 44, 107]. One hypothesis for these differences between studies is that there are unique factors in the gut other than the microbiome that can affect macrophage replacement from blood monocytes but that specific bacterial species present in certain mouse colonies can enhance or decrease the turnover rate.…”
Section: Introductionmentioning
confidence: 99%